The Interplay Between Reproductive Tract Microbiota and Immunological System in Human Reproduction - Al-Nasiry, Salwan; Ambrosino, Elena; Schlaepfer, Melissa; Morré, Servaas A.; Wieten, Lotte; Voncken, Jan Willem; Spinelli, Marialuigia; Mueller, Martin; Kramer, Boris W. (Frontiers in Immunology, 2020)
In the last decade, the microbiota, or set of microorganisms living in and on the human body, has increasingly being attracting the attention of researchers in the medical field. Indeed, since the completion of the Human Microbiome Project, knowledge and interest on the function of microbiota in health and disease, also through the study of its combined genomes, the microbiome, has been steadily expanding. One less explored field of microbiome research has been the female reproductive tract. Research mainly from the past decade suggests that microbial communities residing in the reproductive tract represent a large proportion of the female microbial network and appear to be involved in reproductive failure and pregnancy complications. Overall, such increasing efforts have brought about new scientific evidence, as well as technological and methodological challenges, as detection techniques and analysis methods are far from being standardized. A further hurdle is understanding the complex host-microbiota interaction and the confounding effect of a multitude of constitutional and environmental factors. One key regulator seems to be the immune system that during the peri-conceptional stage, and even more so during pregnancy, modulates this interaction. This review aims at summarizing the current literature on reproductive tract microbiota describing the composition and function of microbiotas in different anatomical locations (vagina, cervix, endometrium and placenta). We also discuss putative mechanisms of interaction between such microbial communities and the different aspects of the immune system focusing on the characteristic immunological changes of normal pregnancy. Furthermore, we discuss how abnormal microbiota “dysbiosis” has been linked to a spectrum of clinical disorders related to the female reproductive system and how the maternal immune system is involved. Finally, based on the data presented in this review, the future perspectives in diagnostic approaches and therapeutic opportunities are explored.